SOD1 protein aggregates stimulate macropinocytosis in neurons to facilitate their propagation. Issue 1 (December 2015) - Zeineddine, Rafaa; Pundavela, Jay; Corcoran, Lisa; Stewart, Elise; Do-Ha, Dzung; Bax, Monique; Guillemin, Gilles; Vine, Kara; Hatters, Danny; Ecroyd, Heath; Dobson, Christopher; Turner, Bradley; et al.
Abstract Background Amyotrophic Lateral Sclerosis is characterized by a focal onset of symptoms followed by a progressive spread of pathology that has been likened to transmission of infectious prions. Cell-to-cell transmission of SOD1 protein aggregates is dependent on fluid-phase endocytosis pathways, although the precise molecular mechanisms remain to be elucidated. Results We demonstrate in this paper that SOD1 aggregates interact with the cell surface triggering activation of Rac1 and subsequent membrane ruffling permitting aggregate uptake via stimulated macropinocytosis. In addition, other protein aggregates, including those associated with neurodegenerative diseases (TDP-43, Httex1 46Q, α -synuclein) also trigger membrane ruffling to gain entry into the cell. Aggregates are able to rupture unstructured macropinosomes to enter the cytosol allowing propagation of aggregation to proceed. Conclusion Thus, we conclude that in addition to basic proteostasis mechanisms, pathways involved in the activation of macropinocytosis are key determinants in the spread of pathology in these misfolding diseases.